Overview of clinical trial protocols for behavioral insomnia in infants - Rayanne Branco dos Santos Lima; Ana Jéssica Lopes Dias; Lorena Pinheiro Barbosa
ABSTRACT Objective: to describe the overview of clinical trial protocols for behavioral insomnia in infants. Methods: an analytical study that reviewed protocols registered with the International Clinical Trials Registry Platform between August and September 2019, aiming to identify the interventions for behavioral insomnia in infants, the comparators, the main primary, secondary outcomes and their respective measurements. Results: eleven protocols registered between 2004 and 2018 were included. Nurses were the main coordinators of protocols (45.5%), with proposals using educational technologies, one-to-one and online follow-up consultations. The main outcome was improvement of infant and maternal sleep patterns. Secondary outcomes were anxiety, depression, and parental sexual satisfaction. To measure them, the following were used: sleep diary (54.5%), actigraphy (45.4%), and the Pittsburgh Sleep Quality Interview (36.3%) and Extended Brief Infant Sleep Questionnaire (27.2%) were used. Conclusion: the protocols proposed interventions for independent sleep, aiming at quality of sleep for the whole family.